Jurnalisme Damai dalam Pemberitaan Ahmadiyah pada Harian Jawa Pos - Andarini, Rindang Senja (Interaksi: Jurnal Ilmu Komunikasi, 2014)
Cikeusik incident attracted many citizens and mediaâ€™s enthusiasm since itâ€™s news worthines. When a violent conflict appear, media supposes to play role in building conflict resolution. This study aimed to examine how Jawa Pos frame and cover violent conflict. This study used qualitative approach with framing analysis method. News coverages about Ahmadiyah from February 7th 2011 till March 11th 2011 was analysed. The result showed that Jawa Pos hasnâ€™t applied peace journalism signed by the usage of victimizing and demonizing language. Jawa Pos preferred dramaticall coverage, used â€œunfavouredâ€ frame and spreaded out stigma to Ahmadiyah and itâ€™s followers.